Journey of a thousand shuttles the Philippine weave - Respicio, Norma Absing (National Commission for Culture and the Arts, 2014)
This a journey that started between eight thousand and four thousand years ago when the first evidence of the presence of weaving technology was discovered in northern Philippines, and which is still endlessly shuttling in widespread key areas in the Philippines to this day, to create the fabric that evince a facet of the craft and artistry of the Filipino people. This book depicts this journey of weaving as each fabric is woven from the backstrap loom, the pedal -driven frame loom, and the tapestry loom, with the ethnic mental templates that exemplify the genius of Filipino weavers.